Technoscientific Angst : Ethics and Responsibility. - Sassower, Raphael (University of Minnesota Press, 1997)
Reassesses the social and ethical situations of technoscientists. What responsibility do the Manhattan Project scientists have for the atomic devastation of Hiroshima? The Krupps scientists for the crematoriums at Auschwitz? Disturbing questions like these are at the heart of this book, a sobering exploration of scientific and intellectual responsibility. Raphael Sassower considers two related phenomena: the positive public image of science as the citadel of truth and objectivity and the angst displayed by scientists over their indirect roles in technological horrors. Largely unexamined, these c.